PENGARUH INVESTASI TIDAK BERWUJUD PADA PROSES BISNIS INTERNAL DAN PEMBELAJARAN PERTUMBUHAN DENGAN PANDEMI COVID-19 SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2021) - Linda Rahmawati; Rita Wijayanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of intangible investment on internal business processes, growth learning and to test the moderating effect of the covid-19 pandemic in this study. . This research is a quantitative study using linear regression analysis with the help of SPSS software. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sampling technique in this study used a purposive sampling method and obtained 56 companies. The results of this study indicate that intangible investment has an effect on internal business processes and learning growth and the interaction of the covid19 pandemic has no effect on internal business processes and learning growth.